Path of infectious diseases in Brazil in the last 50 years: an ongoing challenge - Eliseu Alves Waldman; Ana Paula Sayuri Sato
ABSTRACT In this article, we comment on the main features of infectious diseases in Brazil in the last 50 years, highlighting how much of this path Revista de Saúde Pública could portray. From 1967 to 2016, 1,335 articles focusing on infectious diseases were published in Revista de Saúde Pública. Although the proportion of articles on the topic have decreased from about 50.0% to 15.0%, its notability remained and reflected the growing complexity of the research required for its control. It is noteworthy that studies design and analysis strategies progressively became more sophisticated, following the great development of epidemiology in Brazil in the recent decades. Thus, the journal has followed the success of public health interventions that permitted to control or eliminate numerous infectious diseases - which were responsible, in the past, for high rates of morbidity and mortality -, and also followed the reemergence of diseases already controlled and the emergence of until then unknown diseases, with a strong impact on the Brazilian population, establishing a little predictable and very challenging path.